Terraforming : ecopolitical transformations and environmentalism in science fiction - Pak, Chris (Liverpool science fiction texts and studies ;, 2016)
"This book explores the emergence and development of terraforming in science fiction from H.G. Wells's The War of the Worlds (1898) to James Cameron's blockbuster Avatar (2009). Terraforming is the process of making other worlds habitable for human life. Its counterpart on Earth--geoengineering--has begun to receive serious consideration as a way to address the effects of climate change. This book asks how science fiction has imagined the ways we shape both our world and other planets and how stories of terraforming reflect on science, society, and environmentalism. It traces the growth of the motif of terraforming in stories by such writers as H.G. Wells and Olaf Stapledon in the UK; American pulp science fiction by Ray Bradbury, Robert Heinlein, and Arthur C. Clarke; the countercultural novels of Frank Herbert, Ursula K. Le Guin, and Ernest Callenbach; Pamela Sargent's Venus trilogy; Frederick Turner's epic poem of terraforming, Genesis; and Kim Stanley Robinson's acclaimed Mars trilogy. It explores terraforming as a nexus for environmental philosophy, the pastoral, ecology, the Gaia hypothesis, the politics of colonisation and habitation, tradition, and memory. This book shows how contemporary environmental awareness and our understanding of climate change are influenced by science fiction, and how terraforming in particular has offered scientists, philosophers, and many other readers a motif to aid in thinking in complex ways about the human impact on planetary environments. Amidst contemporary anxieties about climate change, terraforming offers an important vantage from which to consider the ways humankind shapes and is shaped by its world."--Page 4 of cover